TEORI AKOMODASI DAN VARIASI DIALEKTAL DALAM BAHASA JAWA PERBATASAN YOGYAKARTA SURAKARTA - SUYATA, PUJI (LITERA, 2015)
<img src="data:image/png;base64,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